Lithium ion battery electrolyte and lithium ion battery
By using a combination of propylene carbonate and fluorocyclic carbonate in the lithium-ion battery electrolyte, and adding fluorophosphate and 4-(maleimido)phenyl isocyanate, the problem of oxidation and decomposition of the electrolyte in the nickel-manganese positive electrode material is solved, and the oxidation resistance, low temperature performance and large-scale cycle performance of the battery are significantly improved.
Patent Information
- Application Number
- CN202510110564.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-23
- Publication Date
- 2025-05-09
AI Technical Summary
When using nickel-manganese positive electrode material in existing lithium-ion batteries, the electrolyte is oxidized and decomposed on the positive electrode surface, resulting in a rapid attenuation of battery capacity and life.
A lithium-ion battery electrolyte is used, including cyclic carbonate and linear esters as solvents, propylene carbonate and fluorocyclic carbonate as main cyclic ester components, and fluorophosphate as additives, and 4-(maleimido)phenyl isocyanate is added to the electrolyte solution.
It improves the oxidation resistance and stability of the electrolyte, reduces the melting point of the electrolyte, improves the low-temperature performance of the battery, and forms a stable interface film on the surface of niobium titanium oxygen anode and lithium nickel manganate, improving the large-scale cycle performance and high-temperature storage life.
Smart Images

Figure BDA0005256557080000071 
Figure BDA0005256557080000091
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of battery materials, and in particular relates to a lithium ion battery electrolyte and a lithium ion battery. Background Art
[0002] Lithium-ion secondary batteries have the advantages of high operating voltage, light weight, no memory effect, low self-discharge rate, long cycle life, and high energy density. They are currently widely used in mobile phones, computers, electric vehicles, etc. In recent years, out of consideration for environmental protection, electric vehicles have been rapidly developed under the promotion of governments and automobile manufacturers, and lithium-ion secondary batteries have become the ideal power source for the new generation of electric vehicles with their excellent performance.
[0003] At present, based on the fast charging demand of lithium-ion batteries, researchers have developed niobium-based negative electrode materials, especially niobium titanium oxide materials. However, the voltage platform of niobium titanium oxide negative electrode materials is greater than 1V. When paired with conventional lithium iron phosphate or ternary materials, the overall voltage platform of lithium-ion batteries drops significantly, and the energy density is not competitive. Therefore, it is necessary to develop high-voltage positive electrode materials to match them.
[0004] The most researched high-voltage material is nickel-manganese cathode material, which is superior to nickel-cobalt-manganese ternary material in cost and thermal stability. However, its potential to lithium is close to 5V, which will cause the electrolyte on the cathode surface to be oxidized and decomposed continuously, resulting in battery capacity loss and rapid life decay. Summary of the invention
[0005] In order to solve the above problems existing in the prior art, the present invention provides a lithium ion battery electrolyte and a lithium ion battery. The technical problem to be solved by the present invention is achieved by the following technical solutions:
[0006] An embodiment of the present invention provides a lithium-ion battery electrolyte, comprising: a solvent, an electrolyte and an additive, wherein the solvent comprises a cyclic carbonate and a linear ester, the cyclic carbonate comprises propylene carbonate and a fluorinated cyclic carbonate, and the additive comprises a fluorinated phosphate.
[0007] In one embodiment of the present invention, the fluorinated cyclic carbonate includes at least one of fluoroethylene carbonate, bisfluoroethylene carbonate, trifluoromethylethylene carbonate, and pentafluoroethylethylene carbonate.
[0008] In one embodiment of the present invention, the fluorophosphate includes at least one of lithium monofluorophosphate, lithium difluorophosphate, lithium difluorobisoxalate phosphate, sodium monofluorophosphate, sodium difluorophosphate, and sodium difluorobisoxalate phosphate.
[0009] In one embodiment of the present invention, the content of propylene carbonate in the solvent is 10-40wt%, the content of fluorinated cyclic carbonate in the solvent is 10-40wt%, and the sum of the contents of propylene carbonate and fluorinated cyclic carbonate in the solvent is 25-50wt%.
[0010] In one embodiment of the present invention, the content of the fluorophosphate in the electrolyte is 0.2-1 wt %.
[0011] In one embodiment of the present invention, the additive further comprises 4-(maleimido)phenyl isocyanate, and the content of the 4-(maleimido)phenyl isocyanate in the electrolyte is 0.1-1 wt %.
[0012] In one embodiment of the present invention, the electrolyte includes at least one of LiPF6, LiClO4, LiFSI, LiTFSI, and LiBF4.
[0013] Another embodiment of the present invention provides a lithium-ion battery, comprising: a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator, wherein the electrolyte is the lithium-ion battery electrolyte described in the above embodiment, wherein:
[0014] The positive electrode sheet and the negative electrode sheet are respectively arranged on both sides of the diaphragm, and the electrolyte infiltrates the positive electrode sheet, the negative electrode sheet and the diaphragm.
[0015] In one embodiment of the present invention, the positive electrode plate includes a positive electrode material, and the positive electrode material includes lithium nickel manganese oxide having a spinel structure.
[0016] In one embodiment of the present invention, the negative electrode plate comprises a negative electrode material, and the negative electrode material comprises a niobium-based negative electrode material.
[0017] Compared with the prior art, the present invention has the following beneficial effects:
[0018] 1. The present invention uses a combination of propylene carbonate and fluorinated cyclic carbonate in a solvent. Compared with conventional electrolytes using ethylene carbonate as cyclic ester dissociation lithium salt, propylene carbonate and fluorinated cyclic carbonate are not easily oxidized to produce gas and have higher stability, which not only greatly improves the oxidation resistance and stability of the electrolyte, but also reduces the melting point of the electrolyte and improves the low-temperature performance of the battery; in addition, the fluorinated cyclic carbonate can partially participate in film formation to generate substances such as lithium fluoride to improve the stability of the negative electrode interface; at the same time, the additive includes fluorinated phosphate, which can form a stable and low-impedance fluorinated phosphate interface film on the surface of niobium titanium oxide negative electrode and lithium nickel manganese oxide, which can not only improve the high-rate long-cycle performance, but also improve the high-temperature performance; therefore, the lithium-ion battery electrolyte can effectively improve the high-rate cycle life, high-temperature storage life and low-temperature performance.
[0019] 2. Adding 4-(maleimido)phenyl isocyanate to the electrolyte of the present invention can not only form a stable interface film at the interface between the positive and negative electrodes to inhibit the occurrence of side reactions, but also capture water and acid in the battery, inhibit the acid from corrosive decomposition of the positive and negative electrode materials, and further improve the cycle and high-temperature storage life of the lithium-ion battery. DETAILED DESCRIPTION
[0020] The present invention is further described in detail below with reference to specific embodiments, but the embodiments of the present invention are not limited thereto.
[0021] A specific embodiment of the present invention provides a lithium ion battery electrolyte, which includes a solvent, an electrolyte and an additive, wherein the solvent includes a cyclic carbonate and a linear ester, the cyclic carbonate includes propylene carbonate and a fluorinated cyclic carbonate, and the additive includes a fluorinated phosphate.
[0022] The fluorinated cyclic carbonate may include at least one of fluoroethylene carbonate, bisfluoroethylene carbonate, trifluoromethylethylene carbonate, and pentafluoroethylethylene carbonate.
[0023] The linear ester may be implemented to include at least one of dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, methyl propyl carbonate, methyl trifluoromethyl carbonate, methyl trifluoroethyl carbonate, ethyl trifluoroethyl carbonate, and bis(2,2,2-trifluoroethyl) carbonate.
[0024] Practically, the fluorophosphate includes at least one of lithium monofluorophosphate, lithium difluorophosphate, lithium difluorobisoxalate phosphate, sodium monofluorophosphate, sodium difluorophosphate, and sodium difluorobisoxalate phosphate.
[0025] Preferably, the content of propylene carbonate in the solvent is 10-40wt%, such as 10%, 15%, 20%, 25%, 30%, 35% or 40%, etc., but is not limited to the listed values. The content of fluorinated cyclic carbonate in the solvent is 10-40wt%, such as 10%, 15%, 20%, 25%, 30%, 35% or 40%, etc., but is not limited to the listed values. The sum of the contents of propylene carbonate and fluorinated cyclic carbonate in the solvent is 25-50wt%, such as 25%, 30%, 35%, 40%, 45% or 50%, etc., but is not limited to the listed values.
[0026] Preferably, the content of the fluorophosphate in the electrolyte is 0.2-1 wt%, such as 0.2%, 0.4%, 0.6%, 0.8%, 1%, etc., but is not limited to the listed values.
[0027] In a specific embodiment, the additive further includes 4-(maleimido)phenyl isocyanate.
[0028] Preferably, the content of 4-(maleimido)phenyl isocyanate in the electrolyte is 0.1-1 wt%, such as 0.1%, 0.3%, 0.5%, 0.8%, 1%, etc., but is not limited to the listed values.
[0029] Preferably, the electrolyte includes at least one of LiPF6, LiClO4, LiFSI, LiTFSI, and LiBF4.
[0030] Preferably, the content of the electrolyte salt in the electrolyte is 10-25 wt%, such as 10%, 12%, 15%, 18%, 20%, 25%, etc., but is not limited to the listed values.
[0031] The specific embodiment of the present invention also provides a lithium-ion battery. The lithium-ion battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator. The positive electrode sheet and the negative electrode sheet are respectively arranged on both sides of the separator, and the electrolyte infiltrates the positive electrode sheet, the negative electrode sheet and the separator. The electrolyte adopts the lithium-ion battery electrolyte described in the above embodiment.
[0032] In practice, the positive electrode plate includes a positive electrode material, and the positive electrode material includes lithium nickel manganese oxide having a spinel structure. Furthermore, the positive electrode material lithium nickel manganese oxide can also be doped with one or more elements selected from Mg, Fe, Co, Y, Sc, Ru, Cu, Mo, Ce, W, Zr, Ca, P, S, F, B, Si and Sr. Preferably, the content of the doping element in the lithium nickel manganese oxide is 0 to 0.2wt%, such as 0%, 0.02%, 0.05%, 0.1%, 0.15%, 0.2%, etc., but is not limited to the listed values.
[0033] Practically, the positive electrode plate includes a conductive agent, a binder and a current collector in addition to the positive electrode material.
[0034] In practice, the negative electrode plate includes a negative electrode material, and the negative electrode material includes a niobium-based negative electrode material, such as a niobium-titanium oxide material.
[0035] Practically, the negative electrode plate includes a conductive agent, a binder and a current collector in addition to the negative electrode material.
[0036] Practically, the conductive agent in the positive electrode sheet and the conductive agent in the negative electrode sheet can be selected from at least one of conductive carbon black, carbon nanotubes, and graphene, but is not limited thereto.
[0037] Practically, the binder in the positive electrode sheet and the binder in the negative electrode sheet can be selected from at least one of polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polystyrene-butadiene rubber and copolymers containing polystyrene-butadiene rubber, polyacrylic acid and copolymers containing acrylic acid, polyacrylates, copolymers containing acrylates, polyacrylonitrile, copolymers containing acrylonitrile, nylon, etc., but is not limited thereto.
[0038] Practically, the current collector in the positive electrode sheet and the current collector in the negative electrode sheet can be selected from at least one of aluminum, titanium, copper, nickel, stainless steel, carbon cloth or carbon paper, but is not limited thereto.
[0039] In practice, the diaphragm is used to isolate electrons and allow metal ions (such as lithium ions) to pass through. The diaphragm can be a traditional electrochemical battery diaphragm, including any one of an organic polymer diaphragm or an inorganic diaphragm. Exemplary, the diaphragm can be selected from but not limited to any one of a polyethylene porous film, a polypropylene porous film, a polyethylene-polypropylene double-layer porous film, a polypropylene-polyethylene-polypropylene three-layer porous film, a glass fiber porous film, a non-woven porous film, an electrospun porous film, a PVDF-HFP porous film and a polyacrylonitrile porous film. Among them, the non-woven porous film can be selected from polyimide nanofiber nonwoven fabric, polyethylene terephthalate (PET) nanofiber nonwoven fabric, cellulose nanofiber nonwoven fabric, aramid nanofiber nonwoven fabric, nylon nanofiber nonwoven fabric or polyvinylidene fluoride (PVDF) nanofiber nonwoven fabric. The electrospun porous film can be selected from polyimide electrospun membrane, polyethylene terephthalate electrospun membrane or polyvinylidene fluoride electrospun membrane.
[0040] In this embodiment, by using a combination of propylene carbonate and fluorinated cyclic carbonate in a solvent, compared with the conventional electrolyte using ethylene carbonate as the cyclic ester dissociation lithium salt, propylene carbonate and fluorinated cyclic carbonate are not easily oxidized to produce gas and have higher stability, which not only greatly improves the oxidation resistance and stability of the electrolyte, but also reduces the melting point of the electrolyte and improves the low-temperature performance of the battery; in addition, the fluorinated cyclic carbonate can partially participate in film formation to generate substances such as lithium fluoride to improve the stability of the negative electrode interface; at the same time, the additive includes fluorinated phosphate, which can form a stable and low-impedance fluorinated phosphate interface film on the surface of the niobium titanium oxide negative electrode and the lithium nickel manganese oxide, which can not only improve the high-rate long-cycle performance, but also improve the high-temperature performance; therefore, the lithium-ion battery electrolyte can effectively improve the high-rate cycle life, storage life and low-temperature performance.
[0041] The electrolyte of the present invention adds 4-(maleimido)phenyl isocyanate, which contains a cyclic amide bond, a carbon-carbon double bond and an isocyanate group, can undergo an electrochemical polymerization reaction, and form a stable interface film at the interface of the positive and negative electrodes to inhibit the occurrence of side reactions, reduce the consumption of lithium ions, thereby reducing the damage to the positive and negative electrode structures, and improving the storage life and high-rate cycle performance of the lithium ion battery; in addition, due to the isocyanate group, it can react with water and acid in the battery, inhibit the corrosion and decomposition of water and acid on the positive and negative electrode materials, thereby further improving the cycle and high-temperature storage life of the lithium ion battery.
[0042] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0043] In the embodiments and comparative examples of the present invention, the materials used to prepare the electrolyte are as follows:
[0044] Solvents: propylene carbonate (PC), ethylene carbonate (EC), ethyl methyl carbonate (EMC), fluoroethylene carbonate (FEC), bisfluoroethylene carbonate (DFEC);
[0045] Electrolyte salt: LiPF6;
[0046] Additives: lithium monofluorophosphate (A1), lithium difluorobisoxalate phosphate (A2), sodium difluorophosphate (A3), 4-(maleimido)phenyl isocyanate (A4).
[0047] Examples 1 to 18 of the present invention are all prepared in sequence according to the following preparation method to obtain electrolyte:
[0048] First, in a glove box, slowly add electrolyte lithium salt to the mixed solution of solvent, add additives after the temperature in the container drops to room temperature, mix well, and prepare an electrolyte. The content and type of each solvent in the electrolyte solvent are shown in Table 1, and the content of electrolyte salt LiPF6 in the electrolyte is 14wt%. The type and content of additives in the electrolyte are shown in Table 1, wherein the content of additives is the weight percentage based on the total weight of the electrolyte, and lithium monofluorophosphate is represented as "A1" in the table, lithium difluorobisoxalate phosphate is represented as "A2" in the table, sodium difluorophosphate is represented as "A3" in the table, and 4-(maleimido)phenyl isocyanate is represented as "A4" in the table. In addition, the order of the content of each solvent in Table 1 is the same as the order of the names of each solvent.
[0049] Comparative Example 1 An electrolyte was prepared according to the following preparation method:
[0050] First, in a glove box, slowly add lithium salt to the mixed solution of solvent, add additives after the temperature in the container drops to room temperature, and mix well to prepare an electrolyte. The content and type of each solvent in the electrolyte solvent are shown in Table 1, and the content of electrolyte salt LiPF6 in the electrolyte is 14wt%. The type and content of additives in the electrolyte are shown in Table 1, where the content of additives is weight percentage based on the total weight of the electrolyte.
[0051] Table 1: Composition of additives in the electrolytes of Examples 1 to 18 and Comparative Example 1
[0052]
[0053] Preparation of lithium-ion batteries:
[0054] The electrolytes obtained in the examples and comparative examples were respectively applied to lithium ion batteries for performance testing, wherein the lithium ion batteries were prepared by the following steps:
[0055] (1) Preparation of positive electrode sheet
[0056] The positive electrode material is lithium nickel manganese oxide (LiNi 0.5 Mn 1.5 O4), binder (polyvinylidene fluoride), and conductive agent (conductive carbon black) are mixed in a mass ratio of 95:2:3, and N-methylpyrrolidone (NMP) is added and stirred to form a positive electrode slurry. Then the positive electrode slurry is evenly coated on the aluminum foil, and the coated aluminum foil is dried at room temperature and transferred to a 130°C oven for drying, followed by cold pressing, trimming, cutting, and striping, and then welding the pole ears to form a positive electrode sheet.
[0057] (2) Negative electrode sheet preparation
[0058] The negative electrode material niobium titanium oxide (TiNb2O7), binder (polyvinylidene fluoride), and conductive agent (conductive carbon black) are dissolved in N-methylpyrrolidone (NMP) at a mass ratio of 95:2:3 and mixed evenly to form a negative electrode slurry. The negative electrode slurry is then evenly coated on the current collector copper foil, then dried at 130°C, and then cold pressed, trimmed, cut, and striped, and the tabs are welded to form a negative electrode sheet.
[0059] (3) Preparation of lithium-ion batteries
[0060] The positive electrode sheet, negative electrode sheet and separator are wound into a bare battery cell and then loaded into an aluminum-plastic film. Then, the cells are baked at 100°C to remove water, and then the corresponding electrolyte is injected and sealed. After standing, hot and cold pressing, formation, exhaust, and capacity separation, a lithium-ion battery is obtained.
[0061] The lithium-ion battery obtained above was subjected to lithium-ion battery performance tests, including the following performance tests:
[0062] (1) Lithium-ion battery high rate cycle test at 25°C
[0063] First, the lithium-ion battery was allowed to stand at 25°C for 30 minutes, discharged at a constant current of 1C to 1.5V, and then allowed to stand for 5 minutes; then charged to 3.6V at a constant current of 5C, further charged at a constant voltage of 3.6V to a current of 0.1C, allowed to stand for 5 minutes, and then discharged to 1.5V at a constant current of 5C. This is a charge and discharge cycle process, and the discharge capacity obtained is the discharge capacity Ca of the lithium-ion battery. After that, 1000 charge and discharge cycles were performed, and the discharge capacity of the 1000th cycle was recorded as Cb.
[0064] The capacity retention rate (%) of a lithium-ion battery after 1000 cycles = Cb / Ca.
[0065] (2) Lithium-ion battery storage test at 60°C
[0066] First, let the lithium-ion battery stand at 25°C for 30 minutes; charge it to 3.6V at a constant current of 1C, and further charge it to 0.1C at a constant voltage of 3.6V; then test the volume of the battery using the drainage method, which is the volume before storage V A The lithium-ion battery was then stored at 60°C and the volume of the test battery was taken out every 10 days. It was then charged to 3.6V at a constant current of 1C and further charged to a current of 0.1C at a constant voltage of 3.6V. The battery was taken out after 60 days of storage at 60°C and the volume of the test battery was V B .
[0067] Volume expansion rate of lithium-ion battery after storage at 60°C for 60 days (%) = (V B -V A ) / VA .
[0068] (3) Low temperature discharge test of lithium-ion batteries
[0069] First, let the lithium-ion battery stand at 25°C for 10 minutes, charge it to 3.6V at a constant current of 1C, then charge it to 0.1C at a constant voltage of 3.6V, and then discharge it to 1.5V at a current of 1C. The discharge capacity at this time is recorded as C. A ; Then charge to 3.6V at a constant current of 1C, and further charge to 0.1C at a constant voltage of 3.6V. Then stand at -30℃ for 60min, and discharge to 1.5V at a constant current of 1C. The discharge capacity at this time is recorded as C B .
[0070] Lithium-ion battery discharge capacity retention rate at -30°C (%) = C A / C B .
[0071] The performance test data of the lithium ion batteries of the embodiments of the present invention and the comparative examples are shown in Table 2.
[0072] Table 2: Lithium-ion battery performance test results
[0073]
[0074] It can be concluded from Example 1 and Comparative Example 1 in Table 2 above that by using solvent PC and fluorocarbonate FEC to replace EC, the 25°C high-rate cycle capacity retention rate, 60°C high-temperature storage volume expansion rate and -30°C low-temperature discharge capacity retention rate are all significantly improved; this is because the replacement of the solvent significantly improves the oxidation resistance of the electrolyte, inhibits the oxidation gas production of the solvent and the consumption of active lithium ions, and in addition, the melting points of PC and FEC are lower than those of conventional EC solvents, thereby improving the low-temperature discharge performance.
[0075] From Examples 1 to 8 in Table 2 above, it can be concluded that the sum of the contents of PC and fluorocarbonate FEC is too low or too high, which will affect the comprehensive performance of lithium-ion batteries. If the PC content is too low, the thermal stability and oxidation stability of the electrolyte will be reduced, and the cyclic ester containing an appropriate amount of PC can reduce the melting point, so too low will affect the high-temperature performance and low-temperature performance; too high PC content will reduce the ability of the cyclic ester to dissociate lithium salts, and will also affect the performance of high-rate cycles. If the content of fluorocarbonate FEC is too low, the dielectric constant of the cyclic ester will also be significantly reduced, and an appropriate amount of FEC can partially participate in the formation of the negative electrode interface film to improve the stability of the interface, which will affect the performance of high-rate cycles; if the FEC content is too high, HF will be lost at high temperatures, affecting the stability of the electrolyte and the positive and negative electrode interfaces, especially significantly deteriorating the high-temperature performance of lithium-ion batteries.
[0076] It can be concluded from Examples 1 and 9 to 11 in Table 2 above that an appropriate amount of fluorophosphate can improve the 25°C high-rate cycle capacity retention rate, 60°C high-temperature storage volume expansion rate, and -30°C low-temperature discharge capacity retention rate of the lithium-ion battery. If the fluorophosphate content is too high, it will not only fail to completely dissociate in the electrolyte to form insoluble matter, but also reduce the conductivity of the electrolyte, which will deteriorate the high-rate cycle and low-temperature performance of the lithium-ion battery.
[0077] It can be concluded from the above Table 2, Examples 1, 12 to 15, that as the content of 4-(maleimido)phenyl isocyanate increases, the high temperature storage volume expansion rate of lithium ion batteries improves significantly, especially because 4-(maleimido)phenyl isocyanate contains maleimido groups that can form dense interface films on the positive and negative electrode surfaces. In addition, the cyano groups it contains can also stabilize the positive electrode surface and reduce the activity of the positive electrode surface, and comprehensively inhibit the oxidation and gas production of the electrolyte on the positive electrode surface, thereby improving high temperature performance. However, if the content of 4-(maleimido)phenyl isocyanate is too high, it will significantly increase the interface impedance of the positive and negative electrodes, thereby deteriorating the high rate cycle and low temperature performance of lithium ion batteries.
[0078] It can be concluded from Examples 16 to 18 in Table 2 above that different contents of PC, different fluorocarbonates, different fluorophosphates and 4-(maleimido)phenyl isocyanate can all yield excellent performance results, but different combinations have more obvious effects on specific performance improvements.
[0079] The above contents are further detailed descriptions of the present invention in combination with specific preferred embodiments, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the concept of the present invention, which should be regarded as falling within the protection scope of the present invention.
Claims
1. A lithium ion battery electrolyte, characterized in that: include: Solvent, electrolyte and additives, the solvent includes cyclic carbonate and linear ester, the cyclic carbonate includes propylene carbonate and fluorinated cyclic carbonate, and the additive includes fluorinated phosphate.
2. The lithium ion battery electrolyte according to claim 1, characterized in that: The fluorinated cyclic carbonate includes at least one of fluorinated ethylene carbonate, bisfluoroethylene carbonate, trifluoromethylethylene carbonate, and pentafluoroethylethylene carbonate.
3. The lithium ion battery electrolyte according to claim 1, characterized in that The fluorophosphate includes at least one of lithium monofluorophosphate, lithium difluorophosphate, lithium difluorobisoxalate phosphate, sodium monofluorophosphate, sodium difluorophosphate, and sodium difluorobisoxalate phosphate.
4. The lithium ion battery electrolyte according to claim 1, characterized in that: The content of the propylene carbonate in the solvent is 10-40 wt %, the content of the fluorinated cyclic carbonate in the solvent is 10-40 wt %, and the sum of the contents of the propylene carbonate and the fluorinated cyclic carbonate in the solvent is 25-50 wt %.
5. The lithium ion battery electrolyte according to claim 1, characterized in that: The content of the fluorophosphate in the electrolyte is 0.2-1 wt %.
6. The lithium ion battery electrolyte according to claim 1, characterized in that: The additive further comprises 4-(maleimido)phenyl isocyanate, and the content of the 4-(maleimido)phenyl isocyanate in the electrolyte is 0.1-1 wt %.
7. The lithium ion battery electrolyte according to claim 1, characterized in that: The electrolyte includes at least one of LiPF6, LiClO4, LiFSI, LiTFSI, and LiBF4.
8. A lithium ion battery, characterized in that: include: A positive electrode sheet, a negative electrode sheet, an electrolyte and a separator, wherein the electrolyte is a lithium-ion battery electrolyte as claimed in any one of claims 1 to 7, wherein: The positive electrode sheet and the negative electrode sheet are respectively arranged on both sides of the diaphragm, and the electrolyte infiltrates the positive electrode sheet, the negative electrode sheet and the diaphragm.
9. The lithium-ion battery according to claim 8, characterized in that: The positive electrode plate includes a positive electrode material, and the positive electrode material includes lithium nickel manganese oxide with a spinel structure.
10. The lithium ion battery according to claim 8, characterized in that The negative electrode plate includes a negative electrode material, and the negative electrode material includes a niobium-based negative electrode material.